Methylmercury produced in upper oceans accumulates in deep Mariana Trench fauna - Sun, Ruoyu; Yuan, Jingjing; Sonke, Jeroen E.; Zhang, Yanxu; Zhang, Tong; Zheng, Wang; Chen, Shun; Meng, Mei; Chen, Jiubin; Liu, Yi; Peng, Xiaotong; Liu, Congqiang (Nature communications, 2020)
Monomethylmercury (MMHg) is a potent toxin that bioaccumulates and magnifies in marine food webs. Recent studies show abundant methylated Hg in deep oceans (>1000 m), yet its origin remains uncertain. Here we measured Hg isotope compositions in fauna and surface sediments from the Mariana Trench. The trench fauna at 7000–11000 m depth all have substantially positive mass-independent fractionation of odd Hg isotopes (odd-MIF), which can be generated only in the photic zone via MMHg photo-degradation. Given the identical odd-MIF in trench fauna and North Pacific upper ocean (<1000 m) biota MMHg, we suggest that the accumulated Hg in trench fauna originates exclusively from MMHg produced in upper oceans, which penetrates to depth by sorption to sinking particles. Our findings reveal little in-situ MMHg production in deep oceans and imply that anthropogenic Hg released at the Earth’s surface is much more pervasive across deep oceans than was previously thought. Monomethylmercury is a toxin that humans can be exposed to after consumption of seafood in which it has bioaccumulated. Here the authors show that amphipods in the deepest point of the global ocean contain monomethylmercury with surface origins, suggesting rapid sinking of this toxin on particles.